2013
DOI: 10.1111/jcpp.12035
|View full text |Cite
|
Sign up to set email alerts
|

Early sensory over‐responsivity in toddlers with autism spectrum disorders as a predictor of family impairment and parenting stress

Abstract: Background Sensory over-responsivity (SOR) affects many individuals with autism spectrum disorders (ASD), often leading to stressful encounters during daily routines. Methods This study describes the associations between early SOR symptoms and the longitudinal course of restrictions in family life activities and parenting stress across three time points in families raising a child with ASD (n = 174). Covariates were child diagnostic severity, emotional problems, and maternal affective symptoms. At time 1 mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 32 publications
5
63
0
3
Order By: Relevance
“…22 Thus, sensory sensitivity may be an important risk factor for the emergence of pathology. 23 Along these lines, perhaps the most clinically significant finding is that SE is a marker for later psychopathology: children with SE were 1.7 times as likely to have increased symptoms of generalized anxiety disorder at follow-up when controlling for baseline levels. Our findings are consistent with previous studies in young adolescent children that revealed increased internalizing and externalizing symptoms 2 ; however, we extend these findings by examining patterns at the syndrome levels, controlling for baseline levels and examining symptoms longitudinally using a structured diagnostic interview.…”
Section: Discussionmentioning
confidence: 99%
“…22 Thus, sensory sensitivity may be an important risk factor for the emergence of pathology. 23 Along these lines, perhaps the most clinically significant finding is that SE is a marker for later psychopathology: children with SE were 1.7 times as likely to have increased symptoms of generalized anxiety disorder at follow-up when controlling for baseline levels. Our findings are consistent with previous studies in young adolescent children that revealed increased internalizing and externalizing symptoms 2 ; however, we extend these findings by examining patterns at the syndrome levels, controlling for baseline levels and examining symptoms longitudinally using a structured diagnostic interview.…”
Section: Discussionmentioning
confidence: 99%
“…These sensory features are some of the most challenging obstacles for parents and children with ASD, limiting adaptive behavior, affecting participation in life activities, and reducing quality of life (Baranek et al 2006;Baker et al 2008;Ben-Sasson et al 2013;O'Neill and Jones 1997;O'Riordan and Passetti 2006;Schaaf et al 2011). Sensory features are now part of the core symptoms under the Restrictive and Stereotypic Behaviors diagnostic criteria for ASD in the DSM 5 (APA 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Qualitative interviews with parents reveal that sensory symptoms limited participation in family routines and activities (Schaaf et al, 2011). Higher rates of sensory behaviors are also related to family and parent stress (Ben-Sasson et al, 2013). The relationship between sensory symptoms and adaptive functioning may depend on the age of participants, the domains of adaptive functioning and sensory processing being compared, and the inclusion of cognitive abilities as an additional covariate.…”
Section: Introductionmentioning
confidence: 99%